Fruit characteristics of peaches produced in El Peñón de Gabante, Estado Aragua, Venezuela (Bioagro, 2020)
There are more than 600 peach cultivars in the world, which has been product of improvement. The absence of an adequate evaluation of fruit quality and a selection program of materials suggests that this variability is not reflected in Venezuela. The objective of this research was to evaluate fruit quality characteristics of some peaches cultivars produced in an orchard in 'El Peñón de Gabante', Aragua state, Venezuela. The cultivars evaluated were 'Amarillo', 'Parcho', 'Melocotón ½ Kilo' and 'Jarillazo'. During the 2013 and 2014 years, approximately 35 kg of fruits per year and cultivar were harvested at physiological maturity and the physical (including color) and chemistry routine characteristics were determined. A completely randomized design was used and cultivars were evaluated in each year of harvest. Analysis of the variance and Tukey test for mean comparison were performed, and summary tables were elaborated for each year considered. There was cultivar influence on the physical characteristics. There was a predominance of low fresh mass, small size and low proportion of pulp (mesocarp) and seeds. Fruits of the reddish cultivars presented lesser brightness, purity and intensity than the yellow ones. Chemical characteristics were also affected by the cultivar. There was a predominance of high values of soluble solids and SS/AT ratio, and low values of total acidity. For the Venezuelan market, 'Melocoton ½ Kilo' is suggested as fresh fruit, and 'Parcho' for processing, and possibly, as fresh fruit.
Keywords: Fruit quality; peach cultivars; plant breeding; Prunus persica